Validation by Magnetic Resonance Imaging of the Diagnostic Potential of a Heptapeptide-Functionalized Imaging Probe Targeted to Amyloid-β and Able to Cross the Blood-Brain Barrier. - André, Séverine; Ansciaux, Emilie; Saidi, Elamine; Larbanoix, Lionel; Stanicki, Dimitri; Nonclercq, Denis; Vander Elst, Luce; Laurent, Sophie; Muller, Robert N; Burtea, Carmen (J Alzheimers Dis, 2017)
The diagnosis of Alzheimer's disease (AD) is a critical step in the management of patients. We have developed a non-invasive diagnosis tool based on magnetic resonance molecular imaging (MRMI) of amyloid-β peptide using ultra-small particles of iron oxide (USPIO) functionalized with a disulfide constrained cyclic heptapeptide (PHO) identified by phage display (USPIO-PHO). After previously demonstrating the optimal pharmacologic properties of USPIO-PHO and its capacity to cross the blood-brain barrier (BBB), the ability of USPIO-PHO to target amyloid plaques (AP) by MRMI has been validated in the present work on AD transgenic mice. The immunohistochemistry and immunofluorescent detection of USPIO-PHO on brain sections collected after in vivo MRMI studies enabled its colocalization with AP, confirming the BBB passage and specific targeting. The AP targeting by USPIO-PHO has been moreover corroborated by the good correlation between the number of AP detected with anti-amyloid β antibody and Perls'-DAB staining. Finally, the crossing mechanism of USPIO-PHO through the BBB was elucidated, revealing the involvement of non-degradation pathway of caveolae, while the control contrast agent USPIO-PEG was not endocytosed by the human brain endothelial cells.